Metabolic Syndrome and Aggravated Cardiometabolic Parameters among Nepalese Adults with Subclinical Hypothyroidism - Lamichhane, Anit; Gautam, Dipika; Khadka, Anil; Bista, Sahara; Khanal, Sudip; Joshi, Govardhan; Bista, Pabitra; Acharya, Aashish; Gautam, Sujan; Thakur, Rajesh Kumar; Bhatt, Mahendra Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Subclinical hypothyroidism (SCH) and metabolic syndrome (MetS) both prevalent disorders associated with an elevated risk of cardiovascular disease (CVD). Thyroid hormones are crucial regulators of lipid and glucose metabolism, suggesting a significant pathophysiological link between SCH and the components of MetS. This study aimed to determine the burden of MetS among individuals with SCH in a Nepalese cohort. Method: Cross-sectional study of 111 adults (≥18 years) undergoing thyroid function tests at Manmohan Memorial Teaching Hospital, Kathmandu (October 2021–March 2022). Participants were classified as euthyroid (n=35), SCH (n=57), or hyperthyroid (n=19). Blood pressure, BMI, and WC were measured, and biochemical parameters FBS, lipid profile, and Thyroid profile were estimated by a fully automated biochemistry analyzer and chemiluminescence immunoassay. MetS was defined according to the NCEP ATP III criteria. Analysis used done in SPSS v23 using ANOVA, post-hoc tests, t-tests, and Pearson’s correlation (p<0.05). Results: Subclinical hypothyroidism exhibited dyslipidemia (elevated TC, TG, LDL-C; reduced HDL-C) and higher BMI versus euthyroid and hyperthyroid groups (p<0.01). Among thyroid disorders, the majority (71.05%) of the cases were with subclinical hypothyroidism (SCH). The overall incidence of MetS was 27.9% where the incidence was higher (90.8%) among females and major (41.94%) affected age group was 36-55 years. The incidence of MetS was higher (35.18%) among SCH (35.18%) as compared to other thyroid disorders. SCH with MetS showed significantly elevated blood pressure, waist circumference, and adverse lipids (p<0.05) as compared to SCH without MetS. TSH was positively correlated with waist circumference (r = 0.325, p = 0.017), implicating TSH in promoting central obesity. Conclusion: Subclinical hypothyroidism is strongly associated with an adverse cardiometabolic profile and a high burden of metabolic syndrome. The coexistence of SCH and MetS identifies individuals with the worst parameters, highlighting a critical subgroup for targeted intervention to reduce diabetes and CVD risk